ANALISIS KEPUASAN PELANGGAN TERHADAP KUALITAS PELAYANAN PADA SWALAYAN AYU NADI PANJER - Asrida, Putu Diah (LPPM IKIP PGRI Bali, 2019)
The purpose of this study is to analyze the extent of customer satisfaction with the quality of customer service. This research method uses Expost Facto, research carried out after the event occurred. This research was carried out at Swalayan Ayu Nadi, which addressed at Jalan Tukad Batanghari, Dauh Puri Klod, West Denpasar. This study will involve 100 respondents, namely consumers who carry out questionnaires in the supermarket Ayu Nadi Panjer. Retail business competition is growing rapidly. Business owners must think of the right marketing strategy to attract customers. Retail business owner Ayu Nadi has taken care of the cleanliness of the area outside and inside the supermarket. Disadvantages that need to be corrected are the attributes contained in Quadrant A. Quadrant A is an attribute that needs to be considered by the company to keep its customers loyal to shop at their company. Placement of product positions and other infrastructure must be a particular concern for retail business owners given the growing number of retail companies. Improvement that needs to be done is the problem of inadequate landfill conditions. Retail business owners must pay attention to the problem of the position of the placement of bins, considering that retail business owners provide land for rest areas. This improvement must be done continuously in order to improve services to make consumers loyal to the products and services provided by business owners.